2015
DOI: 10.1002/jcb.25128
|View full text |Cite
|
Sign up to set email alerts
|

Let‐7f Inhibits Glioma Cell Proliferation, Migration, and Invasion by Targeting Periostin

Abstract: Glioma is one of the most aggressive and malignant tumor types. Despite advances in surgery, imaging, chemotherapy, and radiation, glioma patient prognosis remains poor. Glioma pathogenesis is an urgent problem that must be solved. MicroRNAs (miRNAs) are endogenous small non-coding RNAs that are key post-transcriptional regulators of gene expression. miRNA deregulation commonly occurs in human tumorigenesis. In the present study, the expression levels of Let-7f were down-regulated in both glioma tissues and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 43 publications
(68 reference statements)
5
32
0
Order By: Relevance
“…MiRNAs often suppressed expression of multiple proteins by inhibiting translation or targeting mRNAs at 3′UTR for degradation [19]. According the previous reports, current bioinformatics tools for miRNA-target analysis were widely used in studying association between miRNAs and diseases, including cancer, inflammation, neurodegenerative diseases and epilepsy [12, 13, 15, 20]. These studies indicated these miRNA target prediction tools were effective and accuracy for miRNA target prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MiRNAs often suppressed expression of multiple proteins by inhibiting translation or targeting mRNAs at 3′UTR for degradation [19]. According the previous reports, current bioinformatics tools for miRNA-target analysis were widely used in studying association between miRNAs and diseases, including cancer, inflammation, neurodegenerative diseases and epilepsy [12, 13, 15, 20]. These studies indicated these miRNA target prediction tools were effective and accuracy for miRNA target prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The primers of miRNAs were purchased from RIBO (Guangzhou, China). Real-time PCR for miRNAs was performed according to previous reports in triplicate for each sample [20]. The relative amount of each miRNA was normalized against cel-miR-39-3p by the 2 −ΔΔCt method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Although many mechanisms have been elucidated in the pathogenesis of hypertension, such as endothelial dysfunction, 6 sympathetic nervous system overdrive, 7 inflammatory reactions, 8 oxidative stress, 9 gene modifications and impaired angiogenesis, 10 at the molecular level, many aspects of hypertension development are still unknown. 11 MicroRNAs (miRs) are small non-coding RNAs that are key posttranscriptional regulators of gene expression in all eukaryotic cells 12 and have been found to modulate the function of endothelial cells (ECs), 13 smooth muscle cells 14 and macrophages 15 by controlling the expression of chemokines, thereby affecting different stages of atherosclerosis progression. 16 Specifically, miR-92a has been reported to have a vital role in the development of atherosclerosis by modulating ECs and smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a study has indicated the suppressive influence of let‐7a over‐expression on glioma cell malignancy . Additionally, let‐7f targets periostin has been reported to repress glioma cell invasion, migration, and proliferation . The human miR cluster MC‐let‐7a‐1 ~ let‐7d, including let‐7d, let‐7f‐1, and let‐7a‐1, has been shown to exhibit low levels in hepatocellular carcinoma (HCC) cells .…”
Section: Introductionmentioning
confidence: 99%